Pacu Ekonomi Kreatif dan Pembuatan Sabun Cair di Pusat Informasi & Konseling (PIK) Remaja Share SMP Negeri 7 Medan - Purba, Dianty Putri; Rosmaneliana, Dina; Evadine, Rebecca; Silalahi, Dumariani; Siregar, Achiruddin (Jurnal Pengabdian Pada Masyarakat METHABDI, 2024)
The creative economy has developed in Indonesia since the rise of the digital era. Many people use this as an opportunity to earn more income, such as creating content or selling via social media. Creative economic activities in schools can be something that can be considered to help bridge the future of today's teenage children. Adolescents must know their potential and explore this potential so that it can be developed through creativity. There are several obstacles to the creative economy among young people at SMP Negeri 7 Medan, namely not understanding the creative economy and still lacking skills. Training activities were carried out by giving lectures about the creative economy and then providing practice in making liquid soap. The activities carried out aim to increase the knowledge and skills of young people at SMP Negeri 7 Medan. With this training activity, young people from SMP Negeri 7 Medan have increased their knowledge about the Creative Economy and skills in making liquid soap. All training participants are able to practice making liquid soap well and it is ready to be marketed, thereby increasing their income and helping their family's economy.